Cooperative Learning Approach To Improve Soft Skills Among University Students - Mohd Azmir b Mohd Nizah; Ainurliza Mat Rahim; Adibah Sulaiman @ Mohamad (PHOTONICS, 2024)
This study is aimed to determine whether Cooperative Learning Approach will improve the soft skills among university students and to discover the perception of student towards such approach. Data obtained is analyzed by descriptive as well as inferential statistics. Data on demographic were analyzed by means and percentage, while the paired t-test was used to analyze before and after experiencing Cooperative Learning Approach, in which 0.05 a significant level was established to prove that student’s soft-skills has improved. From 9 key competencies of soft skills that being evaluated, surprisingly result shown that students really improved their soft skills after using Cooperative Learning Approach. In sum, Cooperative Learning Approach can be used as instructional classroom strategy in tertiary education as to improve student’s soft skills and thus increasing their employability chances